PENGARUH EFIKASI EKSTRAK BIJI PINANG DALAM MENGENDALIKAN ULAT DAUN KUBIS PADA PAKCOY - Rezkiyo Suswando; Djamilah Djamilah; Eko Suprijono (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2019)
[THE EFFICACY OF AQUEOUS EXTRACT OF BETEL NUT AGAINST DIAMONDBACK MOTH OF PAKCOY CABBAGES]. The diamondback moth (Plutella xylostella L.) is the most destructive pest on cultivated pakcoy cabbages.  Chemical control using synthetic insecticides may cause pollution to the environment and may contribute to the development of resistance insects.  Therefore, botanical insecticides which are environmentally safe could be used as an alternative pesticide.  The objective of the study was to determine the efficacy of aqueous extract of betel nut to control diamondback moth on pakchoi cabbages (Brassica rapa sub-sp. chinensis). The extracts of betel nut consisted of six concentrations included 20, 30, 40, 50, 60 %, and pure water as a control.  The extracts were sprayed on the pakchoy plants infested by diamondback moth.  The application of betel nut extracts have significantly increased insect’s mortality and decreased the attacked intensity on the cabbages by the insect. The highest mortality of insects was 72.5%, whereas the lowest attack intensity was 6.29% were observed at the concentration of 60% of betel nut extract application. No significant effect was observed on the plant growth and yield.